The Role Of Artificial Intelligence In Analyzing And Interpreting Arabic Texts: Study On The Challenge Of Literal Versus Contextual Meaning/ دور الذكاء الاصطناعي في تحليل النصوص العربية وتفسيرها :دراسة في إشكالية الحمل على اللفظ والمعنى - Kadad, Mustafa; Şehitoğlu, Sadık (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The Arabic language is widely recognized for its complexity and richness. It is distinguished by a sophisticated grammatical and rhetorical system that enables it to precisely convey a wide range of meanings. One linguistic phenomenon that has captured scholars' attention throughout history is the concept of